Capabilities of a new dual beam experiment for simutaneous irradiation of materials with two ion species - Bizyukov, I.; Krieger, K.; Azarenkov, N. (Вопросы атомной науки и техники, 2005)
First experiments showed that simultaneous bombardment with fuel particles and impurities leads to synergistic effects, where the erosion rate of a material cannot be explained by superposition of the separate sputtering processes. For the study of these effects a new Dual Beam Experiment setup has been designed and assembled. This paper describes the design and the accessible range of experimental conditions. Перші експерименти показали, що одночасне бомбардування ізотопами водню і частками домішок приводить до синергетичних ефектів, при яких ступінь ерозії матеріалів не може бути пояснений суперпозицією розпилю¬ вальних процесів. Для вивчення цих ефектів розроблена і змонтована нова двопроменева експериментальна установка. Ця стаття описує її конструкцію і доступні експериментальні можливості. Первые эксперименты показали, что одновременная бомбардировка изотопами водорода и частицами примесей приводит к синергетическим эффектам, при которых степень эрозии материалов не может быть объяснена суперпозицией распылительных процессов. Для изучения этих эффектов разработана и смонтирована новая двух лучевая экспериментальная установка. Эта статья описывает ее конструкцию и доступные эксперимен¬ тальные возможности.